Apraxia de fala x desvio fonético: aspectos Linguísticos e análise acústica da fala na síndrome de Down - Coêlho, Julyane Feitoza (2018)
Down syndrome is a chromosomal disorder caused by trisomy 21. Stomatognathic changes and the linguistic and cognitive difficulties resulting from intellectual deficit found in the person with Down syndrome can have important implications for speech performance, modifying practically all articulatory points of consonants and in some cases compromising motor control during production. This impairment in the ability to voluntarily program speech movements is termed developmental apraxia of speech. In view of this, this study seeks to perform a linguistic analysis of the speech characteristics of individuals with Down syndrome with a diagnosis of childhood apraxia of speech and of phonetic deviation. In addition to describing and characterizing the existing speech and articular alterations at the segmental and suprassegmental levels, using measures of acoustic speech analysis, and correlating the findings with the cognitive, perceptual, linguistic and motor aspects characteristic of Down syndrome. The research is documentary type. Data from ten individuals with Down syndrome, extracted from a pre-established speech corpus. Were used phonetic transcriptions and acoustic analysis were performed using PRAAT software, with the evaluation, description and analysis of aspects related to the alterations found in the speech of these subjects, typology of disfluencies, acoustic measures of vowel formants, voice onset time of occlusives plosives and intonational curve of statements. The study indicated that individuals with Down syndrome and a diagnosis of apraxia, compared to individuals with Down syndrome and a diagnosis of phonetic deviation, presented differentiation in the acoustic measurements of the; presented a considerably higher occurrence of speech disorders, being mainly those of type omission (average of 12.33 occurrences per participant) and substitution (Average of 12,16 occurrences per participant); also showed greater occurrence of disfluencies, mainly of the syllable repetition type; and prosodic changes (83,3%). Regarding acoustic speech analysis, the individual with apraxia evaluated, compared to the participant with phonetic deviation, presented longer duration of voice onset time (VOT), indicating the need for a longer period of time for the production of the consonant plosive occlusive; as well as the presence of a discontinuous intonational curve, with breaks and ruptures, and without the presence of modulations.